Implementasi Blockchain untuk Keamanan Sistem Pembayaran Digital dan Optimasi Transaksi Keuangan (Studi Kasus Industri Fintech di Indonesia) - Rifky Mustaqim Handoko; Budi Aulyansyah Ahmad Trisna; Ryan Delon Pratama; Jadiaman Parhusip (Teknik: Jurnal Ilmu Teknik dan Informatika, 2024)
The implementation of blockchain technology has brought significant changes in the digital payment system, especially in the Indonesian fintech sector. This study aims to explore the benefits of blockchain in improving the security, efficiency, and transparency of financial transactions, while addressing the challenges faced by the fintech industry in Indonesia. With a qualitative descriptive approach supported by secondary data from industry reports, scientific journals, and case studies, this study shows that blockchain is able to reduce the risk of fraud through sophisticated hashing mechanisms and consensus algorithms. In addition, this technology speeds up the transaction process and reduces operational costs by eliminating the need for intermediaries. Immutable data security and high transparency help build user trust, expand financial inclusion, and create a more efficient fintech ecosystem. This study provides a theoretical and practical basis for the development of blockchain-based innovations in Indonesian fintech, which can contribute to the sustainable growth of the digital economy.